2022
DOI: 10.1164/rccm.202204-0657oc
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Coexposure to Extremes of Heat and Particulate Air Pollution on Mortality in California: Implications for Climate Change

Abstract: Rationale Extremes of heat and particulate air pollution threaten human health and are becoming more frequent because of climate change. Understanding the health impacts of coexposure to extreme heat and air pollution is urgent. Objectives To estimate the association of acute coexposure to extreme heat and ambient fine particulate matter (PM 2.5 ) with all-cause, cardiovascular, and respiratory mortality in California from 2014 to 2019. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 45 publications
3
43
2
Order By: Relevance
“…Additionally, a synergistic effect exists between air pollutants and high temperature on health outcomes, which was not adjusted for in this study [ 57 ]. Recent studies have shown that exposure to extreme heat and air pollution has a larger effect on mortality beyond the sum of their individual effects [ 58 ]. Analyzing air pollution data across the state of Queensland is challenging, as it comes with several limitations and confounding variables [ 59 ]; this was outside of the scope of this project.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a synergistic effect exists between air pollutants and high temperature on health outcomes, which was not adjusted for in this study [ 57 ]. Recent studies have shown that exposure to extreme heat and air pollution has a larger effect on mortality beyond the sum of their individual effects [ 58 ]. Analyzing air pollution data across the state of Queensland is challenging, as it comes with several limitations and confounding variables [ 59 ]; this was outside of the scope of this project.…”
Section: Discussionmentioning
confidence: 99%
“…However, the risk of heat-related death varies over space and time as community characteristics, adaptation strategies, behaviors, and socio-demographics change. Further, EHEs may also co-occur with other environmental stressors such as high levels of ground-level ozone and particulate matter from wildfires (Rahman et al, 2022). Therefore, it is important to understand factors associated with the risk of death during specific EHEs to develop more targeted strategies to protect the health of susceptible populations in different regions.…”
Section: Introductionmentioning
confidence: 99%
“…According to the most recent report of the Intergovernmental Panel on Climate Change, the frequency, intensity, and duration of extreme heat events are projected to continue to increase through the twenty-first century, with all regions expected to experience unprecedented temperatures [ 1 ]. These events have been associated with increased heat-related morbidity and mortality [ 2 , 3 , 4 , 5 , 6 , 7 ]. Rising temperatures have been directly connected to human health through heat-related illnesses (e.g., heat exhaustion, heat syncope, and heat stroke), resulting in a marked increase in hospital admissions and mortality rates, although these increases are influenced by variations in exposure, location, and susceptibility [ 8 ].…”
Section: Introductionmentioning
confidence: 99%